Combinatorial Optimization and Applications 6th International Conference, COCOA 2012, Banff, AB, Canada, August 5-9, 2012. Proceedings - Lin, Guohui; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 6th International Conference, COCOA 2012, held in Banff, Alberta, Canada, in August 2012. The 33 revised papers including one invited talk and one keynote talk were carefully reviewed and selected from 57 submissions. The papers are focused to theoretical results and also on recent works on experimental and applied research of general algorithmic interest.
Keywords: Computer science; Computer Communication Networks; Computer software; Electronic data processing; Computational complexity; Algorithms; Computer Science; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Numeric Computing; Algorithms; Computer Communication Networks